Implementation of HSV Imagery with K-Nearest Neighbor for Classification of Maturity Levels in Tomatoes - Lailatul Husna Aulia; Fazar Azhari; Muhammad Dhuha Bimantara (Ali Institute of Reseach and Publication, 2023)
The tomatoes used use tomatoes (Lycopersicum esculentum Mill) which is a type of horticultural plant. One type is plum tomatoes. The process of classifying tomato ripeness is carried out manually through direct visual observation. However, this is very difficult to do because it is inconsistent. Therefore, relevant features are needed to classify tomato maturity levels based on HSV features using the KNN method. The method used in classification is K-Nearest Neighbor, this algorithm requires features to build the model. The feature used is HSV feature extraction. Based on the results of research tests carried out, it proves that Euclidean distance k=2 has a percentage value of 85%. Based on the level of accuracy, the color feature k=2 shows the best k value in classifying tomato ripeness levels measuring 400x400 pixels. To achieve a high level of accuracy, image processing time should be less